Water and beverage consumption patterns among 4 to 13-year-old children in the United Kingdom - Florent Vieux; Matthieu Maillot; Florence Constant; Adam Drewnowski (BMC, 2017)
Abstract Background The UK government has announced a tax on sugar-sweetened beverages. The aim of this study was to assess consumption patterns for plain drinking water relative to sugary beverages among UK children. Methods Dietary intake data for 845 children aged 4-13 years came from the nationally representative cross-sectional National Diet and Nutrition Survey, 2008-2011. Beverage categories were drinking water (tap or bottled), milk, 100% fruit juices, soda, fruit drinks, tea, coffee, sports drinks, flavored waters, and liquid supplements. Consumption patterns were examined by age group, gender, household incomes, time and location of consumption, region and seasonality. Total water consumption from drinking water, beverages, and foods, and the water-to-calorie ratios (L/kcal) were compared to the EFSA (European Food Safety Authority) adequate intake standards. Results Total water intake (1338 ml/d) came from plain water (19%), beverages (48%), and food moisture (33%). Plain drinking water provided 258 g/d (241 g/d for children aged 4-8 years; 274 g/d for 9-13 years), mostly (83.8%) from tap. Water and beverages supplied 901 g /d of water. Tap water consumption increased with income and was highest in the South of England. The consumption of bottled water, soda, tea and coffee increased with age, whereas milk consumption declined. About 88.7% of children did not meet EFSA adequate intake standards. The daily water shortfall ranged from 322 ml/d to 659 ml/d. Water-to-calorie ratio was 0.845 L/1000 kcal short of desirable levels of 1.0-1.5 L/1000 kcal. Conclusion Total water intake were at 74.8% of EFSA reference values. Drinking water consumption among children in the UK was well below US and French estimates.